Changes in volatile profiles of a refrigerated‐reheated xylose‐cysteine‐lecithin reaction model analyzed by GC×GC‐MS and E‐nose. Issue 3 (4th February 2022) - Zhang, Zheqi; Zang, Mingwu; Zhang, Kaihua; Li, Dan; Wang, Shouwei; Li, Xiaoman; Zhou, Huimin; Zhang, Xi
Abstract : Abstract: The changes in the volatile profiles of a xylose‐cysteine‐lecithin reaction model were investigated by using comprehensive two‐dimensional gas chromatography–mass spectrometry (GC×GC‐MS) in combination with headspace solid‐phase microextraction (SPME) and electronic nose (E‐nose) to evaluate the contribution of refrigerating and reheating treatment to warmed‐over flavor (WOF). The volatile compound results and E‐nose revealed that the contribution of refrigerating and reheating to the WOF was not consistent. After refrigerating, the level of furfuryl mercaptan increased, while that of 1‐octene‐3‐ol, octanal, nonanal, and 2‐decanone decreased, which affected the flavors. An increase in the level of 1‐octene‐3‐ol, 2‐pentyl‐thiophene, and hexanoic acid and a decrease in the levels of furfural, 2‐methyl‐3‐furanthiol, and 2‐methyl‐3‐pentanethiol occurred during reheating. According to the odor activity value and sensory evaluation, the sulfur‐like odor became more intense after refrigerating, while the rancid‐like odor grew stronger, but the sulfur‐like odor alleviated after reheating. Overall, the reaction between residual substances caused the WOF during refrigeration, also lead to the fatty acid oxidation increased after reheating. The overproduction of fatty acids oxidation products and decreased of volatile product of Maillard reaction leads to the WOF during reheating. Practical Application: This study provides theoretical guidance to reduce the off‐flavors of meat products.